Tata Kelola Badan Usaha Milik Desa “Wijaya” Desa Bejijong Kecamatan Trowulan Kabupaten Mojokerto - Dhohan, Ajie; Nawangsari, Ertien Rining (Universitas Batanghari Jambi, 2024)
The development of the potential of the village-owned business sector is currently a special attraction in Indonesia. One of them is the governance process carried out by the Village-Owned Enterprise